Current management of non‐alcoholic steatohepatitis. (20th February 2020) - Muthiah, Mark D.; Sanyal, Arun J.
Abstract: Non‐alcoholic steatohepatitis (NASH) is the most common cause of liver disease in Western populations, and its prevalence is increasing rapidly. It is part of a multisystem disease affecting other organs such as the kidneys, heart and blood vessels, and is closely associated with the components of the metabolic syndrome. Physicians managing patients with NASH should not only focus on the management of NASH, but also on associated comorbidities in individual patients. The approaches to treatment of NASH include either limiting energy surplus alone, or in combination with targeting of downstream pathways of inflammation and fibrosis. In this mini‐review, we discuss the currently available treatment options for NASH, as well as those in late‐stage clinical trials. We discuss the challenges of managing these patients with a limited number of approved therapies, as well as managing advanced‐stage patients with NASH and cirrhosis. We also discuss the specific management of comorbidities in NASH patients, in particular diabetes, hypertension, dyslipidaemia and cardiovascular diseases. Finally, we present the screening protocols for both hepatocellular carcinoma and extrahepatic malignancies in these patients.